Prévalence de la maladie coeliaque à Mostaganem (1996-2008) et diététique associée auprès des patients de l’EPH Ain Tedeles de Mostaganem (2009) - AMAMRA, Soumia (My University, 2017)
The objectives of this work are the estimation of the prevalence of celiac disease at Mostaganem city and the study of the associated dietetics. I am carried out a retrospective analysis of all patients with celiac disease residing in Mostaganem city who were listed in the records of different health care services between 1996 and 2008. The survey on associated dietetics was conducted with 100 patients followed at the EPH Ain tedeles. I am searched information on the gluten-free diet, dietary management and dietary habits of the patients. An increase in the prevalence of the celiac disease from 0,11‰ in 1996 to 0,97‰ in 2008 was noted. This number found at the end of the study period is less than the number estimated for the Algerian North (1,33‰) while remaining below the number given for North Africa (1,4‰) and very far from that given for the world(10‰). We found that the prevalence of celiac disease is higher in female subjects (for all years of study) and in subjects aged 10-14 years and those aged 15-19 years (at the end of the study period). I am observed that more than three quarters of the patients follow strictly the gluten- free diet. The high cost of gluten-free products remains the main difficulty related to the follow-up of the diet. The difficulty of eating outside the home, lack of conviviality of alimentation, lack of appetite and psychological problems are the main consequences caused by the gluten-free diet. Foods that celiac patients require are in first position bread, couscous in the pasta category and traditional cakes in the cakes category. The galette and gluten-free cakes are the two main foods made at home. As for commercially gluten-free foods, bread, pasta and semolina and/or flour are the most purchased.
Keywords: Celiac disease; prevalence; Mostaganem; dieteti; Maladie coeliaque; prévalence; diététique.